Análise sensorial como ferramenta útil no desenvolvimento de cosméticos - Isaac, Vera Lucia Borges [UNESP]; Chiari, Bruna Galdorfini [UNESP]; Magnani, Caroline [UNESP]; Correa, Marcos Antonio [UNESP] (My University, 2012)
In assessing the quality of cosmetics, sensory analysis has an undisputed role as a tool of scientific measurement, since no analytical tool is capable of replacing the human senses. In product development, sensory analysis is a uniquely useful tool to measure consumer acceptance. The objective of this paper is to present a critical review of the issue based on published papers and sensory test results obtained by our research group, which can assist cosmetics development.

Na avaliação da qualidade de cosméticos, é indiscutível o papel da análise sensorial como instrumento de medida científica, uma vez que não existe nenhum instrumento analítico capaz de substituir os sentidos humanos. Para o desenvolvimento de produtos, a análise sensorial aparece como uma ferramenta útil para indicar a aceitação do consumidor. O objetivo deste trabalho é apresentar uma revisão crítica do assunto, baseada em artigos publicados e em resultados de testes sensoriais obtidos por nosso grupo de pesquisa, que podem auxiliar no processo do desenvolvimento de cosméticos.
Sensory analysis as a useful tool in the development of cosmetics
Keywords: Cosmetic development; Cosmetics; Sensory analysis of cosmetics; cosmetic; product development; sensory analysis